Recognition of Advanced Pharmacy Practice Experience Student Participation Within Antimicrobial Stewardship Activities. (February 2015) - Gauthier, Timothy P.; Steinberg, Jennifer G.; Zapantis, Antonia; Aragon, Laura
Background: Antimicrobial stewardship is important in managing patients with infectious diseases. Limited data exist documenting the extent of pharmacy student involvement within antimicrobial stewardship activities.Objectives: The purpose of this study was to document the types of hospital-based antimicrobial stewardship activities in which Advanced Pharmacy Practice Experience (APPE) students are involved.Methods: A questionnaire was developed using the most current guideline for developing an institutional antimicrobial stewardship program. It was designed to collect preceptor-reported perceptions and APPE student involvement in antimicrobial stewardship activities. Pharmacist preceptors of APPE students from 2 Florida Colleges of Pharmacy were surveyed in October 2011. Questionnaires fully completed by hospital pharmacists currently serving as an APPE preceptor were included.Results: Forty-eight questionnaires met all inclusion criteria, collectively reporting APPE student participation within every element of antimicrobial stewardship. The most common areas of student participation were dose optimization based on patient characteristics (n = 40, 83%), acquiring patient information for prospective audit with feedback (n = 39, 81%), intravenous to oral conversion (n = 37, 77%), and pharmacokinetic services (n = 36, 75%). Anti-infective subcommittee participation (n = 3, 6%) was uncommon. Respondent perceptions were overall favorable regarding student participation in antimicrobial stewardship activities.Conclusion: With supervision from pharmacist preceptors, APPE students from 2 Florida colleges of pharmacy were reported to participate in each element and activity of antimicrobial stewardship as set forth by current guidelines. The role and value of such involvement is not fully understood. Future research investigating activity-specific outcomes and policy creation are needed to guide appropriate use of APPE students as a resource for optimizing antimicrobial use in hospitals.